Aplikasi Rekomendasi Pola Makan Berbasis iOS - Afan Galih Salman; Yen Lina Prasetio; Bayu Kanigoro; Anggi Anggi (Bina Nusantara University, 2012)
The goal for implementing this system is to help users manage and track history about their eat pattern, choose proper food for body’s need, and pick restaurants. Methodology used for this research contains three parts, which is analysis, design, and literature study. In requirement analysis, we do some interview with nutritionist and food provider, analysis iOS user, compare with same kind of application, and identify components that we need. In design method, we use Unified Modelling Language approach, ERD design, and user interface design. The result is a food planning mobile application with iOS platform. This application can help user manage and track their eat pattern, help user choose balanced food that suitable for their body, and inform user where they can get food they plan to eat.